O incêndio das imagens: arte e violência de Estado na América do Sul - Mônica Vaz da Costa (2022)
This thesis aims to investigate images that represent political violence, produced by South American artists since 1980, a period that coincides with the end of dictatorial regimes and with the sequent processes of redemocratization and economic opening in some countries in the region. The violence of the images presented in this investigation does not rest upon its visible aspect, but upon what is behind, beyond its surface, out of sight. It relies upon what is not perceptibile in the image. Thus, the image that bears the brutality of the State is atrocious, and is not necessarily intolerable. We find this aspect in the History and memory evoked by the artistic practices of those who position themselves, in the form of denunciation or manifest, against violent actions and abuses within the exercise of power. In opposition to the mass media images, images that circulate within the context of art (although they are frequently appropriated from newspapers and magazines) are in perspective. For this reason, we observed the works beyond their formal characteristics, relating them to the social and political contexts in which they were produced. Thus, these images emerge as testimonies of brutal events and as antimonuments that spark memories that are often muted, forgotten or ignored.